História do ensino da literatura infantil nos cursos de formação de professores primários no estado de São Paulo, Brasil (1947-2003) - Oliveira, Fernando Rodrigues de [UNESP] (2014)
In this dissertation, we present results of a doctoral study in Education in the scope of the Research Group and the Integrated Research Project “History of Teaching Language and Literature in Brazil”, coordinated by Maria do Rosário Long Mortatti. Aiming to contribute to the understanding of the history of teaching children’s literature and its relation to the history of teacher education, we focus on some aspects related to “teaching to teach” children’s literature on teacher education courses for primary school in São Paulo State. The period is delimited between 1947 and 2003, respectively the first and last years in which we found the presence of “Children’s Literature” as a school subject in the teaching programs of teacher education courses. Through historical approach, focusing on documentary and bibliographical research and using procedures of locating, recovering, assembling, selecting, ordering documentary sources and reading specialized bibliography, we gathered references of different types of texts related to teaching children’s literature in São Paulo State. Among the texts that we found, we selected teaching manuals for the analysis of textual configuration, for being the most representative in relation to the research objectives. This analysis enabled us to understand that: the inclusion of teaching children’s literature in teacher education has been directly related to the construction of a school knowledge about this literary genre that, in the absence of a theoretical or reference knowledge on the subject, proceeded to “work” as a theorization. This school knowledge, formulated and disseminated within teaching children’s literature in teacher education, has been theoretically supported by concepts of Psychology. This has directly contributed to the formation of a concept of children’s literature related to children’s mental development. Finally, with the strength of an ...